Visionary Eyes and Transgressing Voices. The Other in the Travel Narrations Written by the Mansilla Siblings - Pérez Gras, María Laura (Anales de Literatura Hispanoamericana, 2010)
The travel narrations written by the Mansilla siblings, Eduarda y Lucio V., present a common ideology, axial to its analysis and interpretation: it breaks and overcomes the dichotomies set in the cultural life of their time, from which the Argentine society perceived itself (civilization/barbarism, unitaries/federals, the city/the countryside), as we can clearly see in Lucía Miranda and Una excursión a los indios ranqueles. In addition, in their narrations about journeys to remote lands, both writers actively participate in the way the Other sees them; they nourish their work from these images to mold their own identity form similarities and differences, but they also analyse it critically to measure themselves and the Other, for the first time, by means of a Southamerican stick. Furthermore, they both rebuild the image of the Other by generating a cosmopolitan, tolerant, excentric and transforming type of discourse, from which they go beyond the established ideas to irritate the hegemonic groups. In this essay, we shall approach some extracts of these travel narrations to exemplify what has been explained in the previous paragraphs. To do this, we will make use of the theories on travel writing, but from an original perspective, renewed and interdisciplinary, that mainly sets foot on imagological concepts and cultural studies.
Keywords: Mansilla Siblings; Travel Narrations; Imagology; Cultural Studies; Transgressing Ideas